Battery Pack Cells Mon itoring for Intelligent Charging - Beirão, Miguel Duarte (2016)
This dissertation intends to create a system capable of cell charging, cell balancing or both at the same time for batteries with multiple cells connected in series. It also tries to understand why there is only few literature connected with cell balancing and cell charging at the same time. For that purpose, this dissertation presents a review on the state of the art of many concepts related both to balancing and charging in order to pick the right methods and equipment to achieve the objectives of this work. This dissertation includes literature review on batteries, cell balancing methods and topologies, cell charging methods and a small review on state of charge estimation methods. Later on, this document studies and explains hardware and software requirements and choices in order to understand the final developed circuit. Lastly, development difficulties, results and conclusions are presented.